PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA GURU TIDAK TETAP (GTT) DI KECAMATAN MELIAU KABUPATEN SANGGAU - Jumardi Budiman (Jurnal Ekonomi Integra, 2016)
Compensation and motivational aspects are inseparable in human resource management. Compensation and motivation discount linkages and relationships that influence each other in supporting a person's performance. This study seeks to assess the degree of influence between variable compensation on work motivation on temporary teachers in the District Meliau Sanggau. The main problem of this study is: "How the compensation on work motivation of teachers does not remain in the Meliau District?” The method used is quantitative method. The study population was  temporary teachers in the Meliau district 30 people. Namely data collection techniques using indirect communication, direct communication and observation with data collection tool in the form of a questionnaire, interview and observation. Data were analyzed using regression techniques (correlation causality). Based on the survey results revealed that there is an influence of 0.54, or 29.7% of variable compensation to variable work motivation on temporary teachers in District Meliau. The conclusion from this study is that the null hypothesis (H0) was rejected because tcount> t table (3.443> 2.045).